Pengaruh Dukungan Keluarga terhadap Tingkat Depresi Pasien Chronic Kidney Disease Stadium 5D yang Menjalani Hemodialisis di RSD dr. Soebandi Jember (The Influence of Family Support on Depression Level of Chronic Kidney Disease Stage 5D Patient's during H - Devita Luthfia Fitrianasari; Justina Evy Tyaswati; Ida Srisurani Wiji Astuti (Pustaka Kesehatan, 2017)
Chronic Kidney Disease (CKD) is a disease with progressive and irreversible reduction in kidney function. Patient with CKD Stage 5D requires hemodialysis to support their life. Hemodialysis should be conducted for their long life which can be a stressor lead to depression. Therefore, family support is necessary to treat depression in CKD patients. The aim of this study was to analyze the effect of family support on depression level of patient with CKD stage 5D undergoing hemodialysis. This was a correlation analytical study design with cross sectional approach involving 30 correspondents. Data were collected by using HDRS questionnaire to measure patient's depression level and Family Support questionnaire to measure family's support level. Data were analyzed by using Spearman correlation test. The results showed that 50% of respondents had mild depression and 50% of respondents got good family support. Spearman correlation test showed significance (p) of 0.010 with correlation coefficient (r) of -0.462. Thus, we can conclude that there was an influence of family support on depression level of patient with CKD stage 5D undergoing hemodialysis at dr. Soebandi Hospital Jember. The higher the family support, the lower the patient's depression level. Keywords: Chronic Kidney Disease (CKD), Depression, family support, hemodialysis